Framing the Poor: Media Illiteracy, Stereotyping, and Contextual Fallacy to Spin the Crisis - Christian Garland (tripleC: Communication, Capitalism & Critique)
The title of this contribution is a play-on-words: the media’s deliberate stereotypical framing of the poorest section of society, many of whom are claimants of one kind or another, as being the internal social “other”—“not like us”, but also literally attributing—usually indirectly—substantial blame for the ongoing crisis of capitalism to this same group, since it requires very minimal social entitlements for material survival and does not apparently create value. The media framing of this “common sense” simplified account of complex social problems is subject of this article. Whilst media manipulation of a passive and inert readership and/or audience has plenty of critics, this work contends that a Marxist understanding that also uses aspects of Chomsky’s original propaganda model, provides the best resources available for making sense of the mass media’s disingenuous framing and spin of social and political issues such as this in the contemporary UK.media and journalism